Work Posture Risk Analysis Based on Evaluation Results Using the Quick Exposure Check Method - Achmad Ganni Rizaldi; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2022)
UMKM XYZ is an industry engaged in making shoes, the superior product is the type of embroidered shoes. The process of making embroidery shoes requires manual handling by workers so that in the production process there are still a series of non-ergonomic work postures. The work posture assessment method used is the Quick Exposure Check (QEC). The QEC method was chosen because this method is simple and easy to understand and this method also assesses from two points of view, namely worker assessment and observer assessment. Based on this research, the recalculation of the total exposure level of the proposed improvements to work facilities is expected to obtain an exposure level value with a range of <40%. This value means the work station is safe and can reduce musculocetal injuries and increase worker productivity.